2022
DOI: 10.1111/fare.12805
|View full text |Cite
|
Sign up to set email alerts
|

“Her bun in my oven”: Motivations and experiences of two‐mother families who have used reciprocal IVF

Abstract: Objectives: What motivates same-gender female couples to choose reciprocal in vitro fertilization (IVF)? Do their experiences of becoming and being a mother via reciprocal IVF match their pre-parenthood expectations? Background: Reciprocal IVF is a treatment route available to cis, same-gender female couples, and other couples in which both partners have a uterus and egg stores. One partner's egg is retrieved, fertilized in vitro with donor sperm, then carried by the other partner. Existing debate has consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Due to delays caused by Covid, it was decided to terminate recruitment when 30 of such families in each family type had taken part in the study. Findings on mothers’ motivations for, and experiences of, shared biological motherhood for the larger sample are reported elsewhere ( Shaw et al ., 2023 ).…”
Section: Methodsmentioning
confidence: 57%
“…Due to delays caused by Covid, it was decided to terminate recruitment when 30 of such families in each family type had taken part in the study. Findings on mothers’ motivations for, and experiences of, shared biological motherhood for the larger sample are reported elsewhere ( Shaw et al ., 2023 ).…”
Section: Methodsmentioning
confidence: 57%
“…Research on other family types has found that pre-parenthood expectations of couple parenting equality are not always met (e.g. Faircloth, 2021 ; Shaw et al, 2022 ), and this study suggests that such violations of equality expectations can persist when parenting with a friend or acquaintance.…”
Section: Discussionmentioning
confidence: 61%
“…We also know little about platonic co‐parenting, which resists the idea that parenting needs to stem from two romantically or sexually involved partners. Researchers also could explore how LGBTQ parents wrestle with complicated tensions embedded within certain pathways to parenthood, such as transnational surrogacy or transracial adoption (Geerts & Evertsson, 2022; Goldberg et al, 2023; Shaw et al, 2022). Lastly and more foundationally, researchers could begin to pull apart intentions, desires, and motivations for parenthood in the first place.…”
Section: Reimagining Resilience and Resistance In Lgbtq Family Sciencementioning
confidence: 99%